2017
DOI: 10.4236/psych.2017.810095
|View full text |Cite
|
Sign up to set email alerts
|

Verbally Aggressive Instructors and Machiavellian Students: Is the Socio-Communicative Style an Over-Bridging?

Abstract: Goals of this research are: 1) to examine the role of gender, 2) to explore the relationship between perceived instructors' verbal aggressiveness, socio-communicative style and students' Machiavellian tactics, 3) to investigate the influence of instructors' verbal aggressiveness on their socio-communicative style and students' Machiavellian tactics in physical education context and 4) to propose a students' and instructors' typology which will be the final overbridging of verbal aggressiveness and Machiavellia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 80 publications
0
3
0
4
Order By: Relevance
“…It has been argued that the instructors' communication with their trainees has a noticeable effect on the learning process as well as a significant interaction with possible aggressiveness (Bekiari, 2012;2017b;Bekiari, Deliligka, & Hasanagas, 2017;Bekiari, Deliligka, & Koustelios, 2016;Bekiari, Digelidis, & Sakellariou, 2006;2016a,b,c;Bekiari, Hasanagas, Theoharis, Kefalas, & Vasilou, 2015;Bekiari, Kokaridas, & Sakellariou, 2005;2006;Bekiari, Patsiaouras, Kokaridas, & Sakellariou, 2006;Bekiari, Koustelios, & Sakellariou, 2000;Bekiari, Nikolaidou, & Hasanagas, 2017;Bekiari, Pachi, & Hasanagas, 2017;Bekiari & Sakellariou, 2003;Bekiari & Spanou, 2018;Hasanagas, Bekiari, & Vasilos, 2017;Manoli & Bekiari, 2015;Myers & Claus, 2012;Theoharis, Bekiari, & Koustelios, 2017). Argumentativeness is considered to be a cognitive skill which is necessary for a thinking person and thus for our contemporary culture (Kuhn & Crowell, 2011;Osborne, 2010) impacting positively in human communication (Goodboy & Myers, 2012).…”
Section: Argumentativenessmentioning
confidence: 99%
“…It has been argued that the instructors' communication with their trainees has a noticeable effect on the learning process as well as a significant interaction with possible aggressiveness (Bekiari, 2012;2017b;Bekiari, Deliligka, & Hasanagas, 2017;Bekiari, Deliligka, & Koustelios, 2016;Bekiari, Digelidis, & Sakellariou, 2006;2016a,b,c;Bekiari, Hasanagas, Theoharis, Kefalas, & Vasilou, 2015;Bekiari, Kokaridas, & Sakellariou, 2005;2006;Bekiari, Patsiaouras, Kokaridas, & Sakellariou, 2006;Bekiari, Koustelios, & Sakellariou, 2000;Bekiari, Nikolaidou, & Hasanagas, 2017;Bekiari, Pachi, & Hasanagas, 2017;Bekiari & Sakellariou, 2003;Bekiari & Spanou, 2018;Hasanagas, Bekiari, & Vasilos, 2017;Manoli & Bekiari, 2015;Myers & Claus, 2012;Theoharis, Bekiari, & Koustelios, 2017). Argumentativeness is considered to be a cognitive skill which is necessary for a thinking person and thus for our contemporary culture (Kuhn & Crowell, 2011;Osborne, 2010) impacting positively in human communication (Goodboy & Myers, 2012).…”
Section: Argumentativenessmentioning
confidence: 99%
“…Surveys have shown that the desire for control has a negative impact on openness (Zhang, 2020). Furthermore, a survey conducted by Bekiari, (2017) found that teachers' verbal aggression has a positive effect on the desire for control. Additionally, Machiavellian control has been found to have a positive effect on unethical consumer behavior (Chowdhury, 2020).…”
Section: The Desire For Control In Machiavellian Leadershipmentioning
confidence: 99%
“…Consequently, a bivariate analysis was preferred, enabling an overview on all possible relations, to a multivariate analysis (Hasanagas and Bekiari 2015;. Last but not least, for the purpose of revealing behavioral patterns (typology), a Principal Component Analysis (PCA) was implemented (Bekiari 2016;2017a;2017b).…”
Section: Data Processingmentioning
confidence: 99%